Why valence is not enough in the study of emotions: behavioral differences between regret and disappointment - Fructuoso Martinez,Luis (2008)
This paper reflects on the role of emotions in decision-making. The authors stress the limitations of a valence (“positivity” versus “negativity”) based approach. Emotions and their experiential content are synthetically exposed. Research has shown that even closely related emotions - such as regret and disappointment -, whether anticipated or experienced, have differential influences on the behavior of decision makers. This favours emotion-specific research in decision-making context, i.e., the pragmatic “feeling-is-for-doing” approach. We believe the emotional system is the primary motivational system for goal-directed behavior.